PELATIHAN KETERAMPILAN KOMUNIKASI MELALUI KEGIATAN BELAJAR BERBASIS PERMAINAN DI SEKOLAH GUNA MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS 2 SDIT NURUT TAKWA - Surtijah, Endeh; Azzahra, Nurul; Hidayat, Rifa Mutiara (Inspirasi: Jurnal Pengabdian Masyarakat, 2024)
Teaching methods that integrate games as the main learning tool have been implemented in school settings in an effort to increase student engagement and motivation in the learning process. This service programme aims to identify and analyse the extent to which monopoly games can motivate students in teaching and learning activities, improve speaking skills, develop listening skills, train negotiation skills and improve social interaction. Monopoly game can be an effective tool in learning communication in class. This training service programme is practiced directly in class 2 SDIT NURUT TAKWA so that the implementation and evaluation of the monopoly game-based learning programme at this school can take place well because previously the teaching method used by the teacher was only lecture, which made students' learning motivation decrease.